2019
DOI: 10.3390/ijms20020259
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Passive Motion Promotes and Maintains Chondrogenesis in Autologous Endothelial Progenitor Cell-Loaded Porous PLGA Scaffolds during Osteochondral Defect Repair in a Rabbit Model

Abstract: Continuous passive motion (CPM) is widely used after total knee replacement. In this study, we investigated the effect of CPM combined with cell-based construct-transplantation in osteochondral tissue engineering. We created osteochondral defects (3 mm in diameter and 3 mm in depth) in the medial femoral condyle of 36 knees and randomized them into three groups: ED (empty defect), EPC/PLGA (endothelial progenitor cells (EPCs) seeded in the poly lactic-co-glycolic acid (PLGA) scaffold), or EPC/PLGA/CPM (EPC/PLG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Previous animal studies have demonstrated the benefit of CPM use with improved chondrogenesis and reduced cartilage breakdown; however, there is a general lack of clinical data available to support this. 20,38,66,76 The studies evaluated predominantly used time-based protocols, with very few utilizing measurements or patient-specific metrics as checkpoints for progression. RTP timelines were reported inconsistently, and there was notable variation within the reported timelines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous animal studies have demonstrated the benefit of CPM use with improved chondrogenesis and reduced cartilage breakdown; however, there is a general lack of clinical data available to support this. 20,38,66,76 The studies evaluated predominantly used time-based protocols, with very few utilizing measurements or patient-specific metrics as checkpoints for progression. RTP timelines were reported inconsistently, and there was notable variation within the reported timelines.…”
Section: Discussionmentioning
confidence: 99%
“…Previous animal studies have demonstrated the benefit of CPM use with improved chondrogenesis and reduced cartilage breakdown; however, there is a general lack of clinical data available to support this. 20 , 38 , 66 , 76 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16-19 For instance, animal studies using continuous passive have shown earlier resumption of ROM results in improved chondrogenesis, proteoglycan and glycosaminogen synthesis in cartilage as well as decreasing collagen breakdown. 17,20,21 Additionally, early ROM prevents disuse atrophy and prevents knee stiffness, which improve early postoperative outcomes. 22 However, it remains to be seen clinically whether early resumption of ROM is superior to providing a limited-flexion brace, which is claimed to prevent shear forces in the early postoperative phase.…”
Section: Discussionmentioning
confidence: 99%
“…This implant creates a temporary shell for tissue regeneration in osteochondral (OC) defects in the knee joint. 4,34 Furthermore, PLGA has been approved by the US Food and Drug Administration for use as a biomaterial in medical devices in preclinical trials 3,31,35,39 and in the clinical orthopaedic setting, indicating that bench research translates to clinical applications. 36 Appropriate mechanical stimuli (eg, physical therapy exercises) provide joint homeostasis in the anabolic and catabolic cytokines of chondrocytes and directly affect the hyaline cartilage repair process.…”
mentioning
confidence: 99%